A Path-Analytic Study of the Consequences of Role Conflict and Ambiguity - Bedeian, Arthur G.; Armenakis, Achilles A. (Academy of Management Journal, 1981)
The article presents information on a study which investigated the consequences of role conflict and ambiguity for job tension, job satisfaction, and propensity to leave an organization through the use of path analysis. The authors investigated the relationship between role perceptions and work-related attitudes and behavior. A study was conducted in a Veterans Administration Medical Center, of which 202 staff members submitted usable questionnaires. The results found that role perceptions are important in understanding job-related attitudes. They also found that the importance of job satisfaction is important on the perceived desirability of leaving or staying in an organization.